Burr Under the Saddle: How Media Coverage Influences Strategic Change - Bednar, Michael K.; Boivie, Steven; Prince, Nicholas R. (Organization Science, 2013)
In this paper we introduce a new antecedent to the strategic change literature by examining the effect of media coverage on the extent of strategic change. Specifically, we examine how negative media coverage may prompt firms to make changes to their resource allocations and then explore how the makeup of the board and firm performance can moderate this relationship. We develop a theoretical framework to explain why media coverage may affect strategic change and then test our theory with a longitudinal analysis of 250 firms over a four-year period. The empirical results lend support to our theory of media influence on strategic change and suggest that the evaluations of firms by outside constituents may influence the decision making of executives.